The Effectiveness Of Principal Leadership In Managing Conflict Management At SMPI Integral Luqman Al-Hakim Batam - Nurhayati; Abdul Talib Bin Bon (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to assess the effectiveness of the principal's leadership in managing conflict management at SMPI Integral Luqman Al Hakim Batam, focusing on the strategies used by the principal in handling and resolving conflicts between students, teachers, and staff, and how external and internal factors influence the success of conflict management at the school. The research approach used was qualitative with a case study design, which collected data through in-depth interviews with the principal, teachers, staff, and students involved in the conflict situation, as well as participant observation and documentation studies. The results of the study showed that the principal applied an open communication approach, mediation, and problem-solving team in managing conflict, but the challenges faced included time constraints, disagreements between related parties, and lack of adequate resources. The principal's interpersonal skills and empathy greatly influenced the effectiveness of conflict management, although there was still room for improvement in terms of more systematic conflict management. This study concluded that the principal's leadership in managing conflict at SMPI Integral Luqman Al Hakim Batam was quite effective, but there needed to be increased leadership training and interpersonal skills development to create a more harmonious and conducive school environment.